A Longitudinal Career Development Curriculum - Anita Pokorny (Association of American Medical Colleges, 2009)
Abstract Introduction Integrating career development and advising content into undergraduate medical education curricula is a goal of many medical schools. In 2005-2006, the Northeastern Ohio Universities College of Medicine (NEOUCOM) realized this goal by incorporating its career development and advising program into the formal curriculum as a central component of a 4-year longitudinal course. One of five course themes, professional identity development (PID) focuses on medical student career development, lifelong learning skills, personal wellness, and self-care. Methods To advance and plot their PID, students participate in didactic and small-group sessions related to four phases of career development: self-assessment, career exploration, decision making, and implementation. Students work with clinical faculty advisors individually and in small groups to self-reflect and set short- and long-term goals. The success of this program depends on volunteer clinical faculty who are willing to devote time to working with a small group of students over their entire 4 years of undergraduate medical education. A mix of didactic and small-group work followed by an opportunity for reflection is most effective. Students benefit from concrete, hands-on activities. A highly structured format that includes a detailed set of expectations is also beneficial to both students and advisors. Results The PID curriculum was first introduced to the class of 2009 in their M1 year. Short-term results indicate that the curriculum has been successful in increasing student use of the AAMC Careers in Medicine (CiM) website. For example, by December of their M1 year, 68.6% of the NEOUCOM class of 2012 had registered with CiM, as compared to 34.2% of class of 2012 M1 students nationally. Because these students are just now in their M4 year and in the midst of residency interviews, it is difficult to assess the long-term effectiveness of the curriculum. In addition, since this initial implementation, the curriculum has undergone multiple changes based on formal and informal feedback from students and advisors. Discussion The PID component of the curriculum constitutes a unique collaboration between the offices of student affairs and medical education. It has yielded increased student use of CiM tools and activities and promoted clinical faculty involvement in students' career development.